The Populist Voter: A Machine Learning Approach for the Individual Characteristics - K. Peren Arin; Efstathios Polyzos; Marcel Thum (Center for Economic Studies and ifo Institute (CESifo), 2023)
Populist parties recently have shaken Western democracies, yet there is no consensus regarding the characteristics of populist voters. By using large-scale surveys from four European countries (France, Germany, Spain, and the U.K.), we investigate individual determinants of populist voting. Our methodological approach controls for model uncertainty by considering the responses to 100 questions that span social, economic, political, environmental, and psychological dimensions. We also include individual misperceptions across several domains. Our results show that left-wing populist voters are not religious, have lower misperceptions regarding foreign-national prisoners, distrust the police, are open to immigrants from poorer countries, and oppose dismantling the welfare state. The right-wing populist voters oppose incoming, racially diverse immigrants, distrust national and international institutions, and have high misperceptions regarding immigrant crimes and the share of social benefits in the GDP. Contrary to the previous literature, attitudes toward globalization, personality traits, labor-market status, and social media use are not consensus variables for either group.
Keywords: C11; D72; P48; 330; populism; random forest; Bayesian model averaging